Dialyzer reuse: a logical practice in hemodialysis - Kashem, Md Abul; Dutta, Pradip Kumar; Huda, Nurul; Das, Saibal; Yunus, Emran Bin; Chowdhury, Dipti (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: hemodialysis; dialyzer reuse; dialyzer efficacy; economical benefits DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9105 JCMCTA 2011; 22(1): 11-14